2017
DOI: 10.3389/fphys.2017.00514
|View full text |Cite
|
Sign up to set email alerts
|

Endurance Training in Normobaric Hypoxia Imposes Less Physical Stress for Geriatric Rehabilitation

Abstract: Rationale: Evidence suggests that training in hypoxia can be very effective even while requiring less physical effort. We therefore aimed to measure the effect of endurance training under hypoxic conditions on pulmonary and cardiovascular parameters in an elderly population undergoing inpatient rehabilitation.Methods: Forty patients over age 65 years with multiple co-morbid conditions were recruited during a 3-week stay in a geriatric rehabilitation center. Using a randomized, single-blinded, placebo-controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 30 publications
0
28
0
1
Order By: Relevance
“…Only a few studies have examined the effects of long‐term hypoxic training on body composition and health‐related factors in older adults. Pramsohler et al measured the effect of endurance training under hypoxia (F i O 2 = 15.3%) versus normoxia (F i O 2 = 20.9%) for 10–30 min at 80% peak oxygen consumption during a 3‐week period on pulmonary and cardiovascular parameters in an older adult population . They reported that the physical effort required of participants to reach target heart rate reduced significantly (−28%) in HTG compared with NTG, whereas no differences were found in cardiopulmonary function between the groups.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Only a few studies have examined the effects of long‐term hypoxic training on body composition and health‐related factors in older adults. Pramsohler et al measured the effect of endurance training under hypoxia (F i O 2 = 15.3%) versus normoxia (F i O 2 = 20.9%) for 10–30 min at 80% peak oxygen consumption during a 3‐week period on pulmonary and cardiovascular parameters in an older adult population . They reported that the physical effort required of participants to reach target heart rate reduced significantly (−28%) in HTG compared with NTG, whereas no differences were found in cardiopulmonary function between the groups.…”
Section: Discussionmentioning
confidence: 99%
“…Various mechanisms for the beneficial effects of hypoxic therapy have been shown, such as appetite suppression, enhanced ability to transport oxygen to working muscle and improvement of fat oxidation . In addition, exercise in hypoxia imposes less stress on the locomotor systems, while resulting in similar physiological stress . Therefore, hypoxic therapy is a promising modality for successful health promotion in the older obese population.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hypoxic exercise (i. e. exercise under reduced oxygen availability) has been shown to represent a valid alternative to normoxic exercise to provide an adequate training stimulus, promoting beneficial physiological training adaptations as well as positive healthrelated outcomes [5][6][7]. Nowadays, hypoxic exercise is implemented within training programs of different populations [5,[7][8][9]. For instance, hypoxic exercise is adopted to increase the physiological load while reducing the mechanical load both in obese patients [10] and in older adults [8].…”
Section: Introductionmentioning
confidence: 99%